Laboratory rearing of Elaeidobius kamerunicus Faust (Coleoptera: Curculionidae) pollinator of oil palm inflorescence in Malaysia - Zulkefli, M. H. H.; Jamian, S.; Adam, N. A .; Jalinas, J.; Mohd Masri, M. M. (Institute of Physics Publishing, 2022)
This study was conducted to evaluate laboratory rearing of Elaeidobius kamerunicus through observation of its life development and survivability on an artificial diet and anthesising male inflorescence of oil palm as the natural feed. The experiment was the three adopted diets compared with rearing on natural feed toward the survivability and life development of reared larvae Elaeidobius kamerunicus. The AMI of oil palm was the successful diet for the survival of weevil larvae with around 11 days to develop from egg to adult. The improved natural feed is calculated to have a longer time for 50% mortality than the first natural feed, where it had double the time requirement. Moreover, improving the natural feed rearing method had increased survivability from around 20% to almost 50%. Furthermore, they improve natural feed enables shorter life development at 10 days. Thus, this study provided the method for rearing E. kamerunicus through the natural feed for better key survival and management.